2018
DOI: 10.1091/mbc.e17-05-0325
|View full text |Cite
|
Sign up to set email alerts
|

Formin-dependent TGF-β signaling for epithelial to mesenchymal transition

Abstract: The role of distinct actin filament architectures in epithelial plasticity remains incompletely understood. We therefore determined roles for formins and the Arp2/3 complex, which are actin nucleators generating unbranched and branched actin filaments, respectively, in the process of epithelial to mesenchymal transition (EMT). In clonal lung, mammary, and renal epithelial cells, the formin activity inhibitor SMIFH2 but not the Arp2/3 complex activity inhibitor CK666 blocked EMT induced by TGF-β. SMIFH2 prevent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
24
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 61 publications
8
24
0
4
Order By: Relevance
“…To understand how actin could impact the fibrotic transcriptional complex, we treated TGFβ1-induced pro-fibrotic EPCs with the Rho-kinase inhibitor Y27632 35 . Consistent with previous data 30 , TGFβ1 treatment increased actin polymerisation and non-muscle myosin II activity marked by the phosphorylation of its light chain (ph-MLC2, Fig. 4a,b).…”
Section: Mainsupporting
confidence: 92%
See 1 more Smart Citation
“…To understand how actin could impact the fibrotic transcriptional complex, we treated TGFβ1-induced pro-fibrotic EPCs with the Rho-kinase inhibitor Y27632 35 . Consistent with previous data 30 , TGFβ1 treatment increased actin polymerisation and non-muscle myosin II activity marked by the phosphorylation of its light chain (ph-MLC2, Fig. 4a,b).…”
Section: Mainsupporting
confidence: 92%
“…To unravel the mechanisms of the ph-EZH2-mediated pro-fibrotic gene expression, we investigated the potential binding partners of EZH2 upon TGFβ1-induced damage in EPCs. It has been shown that remodelling of the actin cytoskeleton is a major pathway involved in TGFβ1 signalling 30 . Actin is constantly shuttled between the cytoplasm and the nucleus, where it has been shown to associate with the chromatin remodelling complex and POL2 to enhance transcriptional activity 31-33 .…”
Section: Mainmentioning
confidence: 99%
“…Our findings are consistent with recent publications that propose a role for formins in regulating the epithelial mesenchymal transition (EMT). Both formin inhibition with SMIFH2 and depletion of mDia1 and mDia2 prevented TGF-β-induced EMT in lung, mammary, and renal epithelial cells [68]. Others demonstrated the role of formins including FHOD1 and FMNL2 in the morphological changes associated with EMT [68-70].…”
Section: Discussionmentioning
confidence: 99%
“…Both formin inhibition with SMIFH2 and depletion of mDia1 and mDia2 prevented TGF-β-induced EMT in lung, mammary, and renal epithelial cells [68]. Others demonstrated the role of formins including FHOD1 and FMNL2 in the morphological changes associated with EMT [68-70]. In ovarian cancer, decreased E-cadherin expression is associated with peritoneal seeding of tumor cells and lower overall survival rate [43, 71].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inhibiting formins, SMIFH2 was also recently shown to inhibit some myosins (Sellers et al, 2020), and therefore may be better described as an inhibitor of contractile networks. Regardless, targeting formins with SMIFH2 has been a reliable indicator for the involvement of formins in other systems (Fattouh et al, 2015;Rana et al, 2018;Velle and Campellone, 2018).…”
Section: Arp2/3 Complex Activity Is Required For the Assembly Of Actimentioning
confidence: 99%